2004
DOI: 10.1002/lsm.20091
|View full text |Cite
|
Sign up to set email alerts
|

Laser irradiation of the guinea pig basilar membrane

Abstract: Laser irradiation causes immediate alterations in collagen organization within the cochlea that can be visualized with polarization microscopy. These alterations may affect cochlear tuning. Ongoing research is aimed at analyzing the effect of laser irradiation on cochlear function. It is conceivable that this technique may have therapeutic benefits for patients with high-frequency sensorineural hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…We could refer to our animal study results that showed no adverse effects from transmeatal irradiation of 144 J/cm 2 (80 mW/cm 2 x 30 min). It has been reported that LLL irradiation reduced the birefringence within the basilar membrane as well as within other collagen-containing structures of cochlea 16 . The report concluded that these alterations of basement membrane by LLL therapy may affect cochlear tuning and it may benefit for patients with high-frequency sensorineural hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…We could refer to our animal study results that showed no adverse effects from transmeatal irradiation of 144 J/cm 2 (80 mW/cm 2 x 30 min). It has been reported that LLL irradiation reduced the birefringence within the basilar membrane as well as within other collagen-containing structures of cochlea 16 . The report concluded that these alterations of basement membrane by LLL therapy may affect cochlear tuning and it may benefit for patients with high-frequency sensorineural hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…We believe this to be a reasonable assumption. However, our model does not consider other changes in cochlear biomechanics that may also occur, such as an increase in CP stiffness (Wenzel et al, 2004) and a decrease in ST fluid mass (de Boer, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Ren et al used PLM to examine microcirculation in the guinea pig cochlea, 15 whereas Wenzel et al used PLM to examine collagen organization and content within the basilar membrane and other cochlear structures after laser irradiation. 16,17 One of the major drawbacks of standard PLM is that it is not a quantitative technique. The intensity of light observed when a birefringent material is viewed by a polarized light microscope depends on the angle of that material's optic axis relative to the transmission axes of the polarization filters.…”
Section: Introductionmentioning
confidence: 99%